2017
DOI: 10.1097/dcr.0000000000000877
|View full text |Cite
|
Sign up to set email alerts
|

Design and Psychometric Evaluation of the Quality of Life in Patients With Anal Fistula Questionnaire

Abstract: The Quality of Life in Patients with Anal Fistula Questionnaire has proven to be a valid, reliable, and concise tool that could contribute to the evaluation of quality of life among patients with an anal fistula. See Video Abstract at http://links.lww.com/DCR/A368.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 27 publications
0
23
0
7
Order By: Relevance
“…39 The study demonstrated the potential assumptions made by clinicians with regard to the impact of fistula surgery on patients' QoL. More recently, Ferrer-Marquez et al 40 developed a QoL questionnaire in patients with (non-Crohn's) anal fistula; however, major limitations of this study were the testing on a small sample (n=54) of Spanish-speaking patients, and crucially patients were not included in the initial development of the questionnaire. There is no objective patient-centred disease scoring tool for Crohn's perianal fistula and this results in an inability to quantify adequately the effect of Crohn's fistulas on psychosocial well-being and has led to calls to address the unmet need for a disease-specific PROM.…”
Section: Discussionmentioning
confidence: 87%
“…39 The study demonstrated the potential assumptions made by clinicians with regard to the impact of fistula surgery on patients' QoL. More recently, Ferrer-Marquez et al 40 developed a QoL questionnaire in patients with (non-Crohn's) anal fistula; however, major limitations of this study were the testing on a small sample (n=54) of Spanish-speaking patients, and crucially patients were not included in the initial development of the questionnaire. There is no objective patient-centred disease scoring tool for Crohn's perianal fistula and this results in an inability to quantify adequately the effect of Crohn's fistulas on psychosocial well-being and has led to calls to address the unmet need for a disease-specific PROM.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, survivors who received ≥30 Gy of pelvic radiotherapy for the treatment of their primary cancer were especially at risk. Anorectal disease has been shown to affect quality of life in the noncancer population through physical and biopsychosocial impact, 31 including depression and poor selfperception. Survivors more frequently had anorectal strictures than siblings.…”
Section: Discussionmentioning
confidence: 99%
“…Among 54 patients diagnosed with a fistula-in-ano in 2015-2016, Ferrer-Marquez et al 31 noted no improvement in quality-of-life impairment 1 month after a baseline survey was initially administered. Anorectal disease has been shown to affect quality of life in the noncancer population through physical and biopsychosocial impact, 31 including depression and poor selfperception. 32 Finally, in a retrospective study from 2012, Polese et al 27 reported that patients who developed benign strictures after colorectal resection and anastomosis endorsed poorer quality of life 6 or more months after the operation in comparison with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the scale is trustworthy when the following criteria are con rmed. In content validity method, I-CVI > 0.78 and S-CVI/Ave > 0.9 were accepted [47]. The range of correlation coe cient among factors is 0.1-0.6, and the correlation coe cient between factor to and the range of BCS is 0.3-0.8.…”
Section: Validitymentioning
confidence: 99%